Vispārējās vidējās izglītības iestādes vadītāja darbība stratēģiskās vadības procesa īstenošanā - Lange, Aleksandrs (Latvijas Universitāte, 2020)
Izglītības iestādes pieaugošā patstāvība liek skaidri apzināt tās nākotnes attīstības perspektīvas, veidus to realizēšanai un paredz ieviest jaunus vadīšanas paņēmienus. Maģistra darbs izstrādāts ar mērķi analizēt izglītības iestādes vadītāja darbību stratēģiskās vadības procesa īstenošanā vispārējā vidējā izglītības iestādē, lai izstrādātu ieteikumus stratēģiskās vadības procesa īstenošanai. Veicot zinātniskās literatūras avotu, normatīvo dokumentu, attīstības plānu, daļēji strukturēto interviju un izglītības iestāžu darbinieku aptaujas datu analīzi, secināts, ka stratēģiskā vadība izglītības iestādē tiešā veidā neietekmē izglītojamo mācību sasniegumus. Izglītības iestādes vadītājs, īstenojot pilnu stratēģiskās vadības ciklu, var sasniegt iestādes definētos rezultatīvos rādītājus, tostarp izglītojamo sasniegumu kritērijus.

The growing independence of educational institution makes it necessary to clearly identify its future development perspectives, ways to implement them and envisages the introduction of new management techniques. The aim of the master's thesis is to analyse the activities of the head of an educational institution in the implementation of the strategic management process in a general secondary education institution, in order to develop recommendations for the implementation of the strategic management process. Analysis of scientific literature, regulations, development plans, semi-structured interviews and survey data concluded that strategic management in an educational institution does not directly affect the learning achievements of students. By implementing a full cycle of strategic management, the head of an educational institution can achieve the performance indicators defined by the institution, including the criteria for the achievements of students. Keywords: strategy, strategic management in education, activities of the head of an educational institution, achievements of students
Activities of the Head of General Secondary Education Institution in the Implementation of the Strategic Management Process
Keywords: Izglītības vadība; Stratēģija; stratēģiskā vadība izglītībā; izglītības iestādes vadītāja darbība; izglītojamo sasniegumi